Dating on your level: assortative mating based on body condition in an amphibian. Issue 1 (2nd January 2023) - Gould, John; Valdez, Jose W.
Abstract : In animal mating systems, individuals obtain fitness benefits by selecting a mate that increases their chance of reproductive success. Among amphibians, it is generally considered that females select males, primarily based on advertisement calls that signal their size, quality or compatibility. Yet, it is becoming increasingly apparent that amphibians exhibit a wide range of mating systems, including those where assortative mating can occur. Herein, we investigated mate selection in the sandpaper frog, Lechriodus fletcheri ; an Australian anuran that breeds explosively during discrete periods of rainfall over an extended breeding period. We compared the size and condition of amplecting pairs relative to other potential suitors within the available population of reproductively active adults over 3 consecutive breeding years. We found no relationship between the SVL of amplecting pairs and no effect of SVL on amplecting status of males within pools. Instead, the condition of amplecting pairs was positively correlated, leading to positive assortative mating. While there was a general decline in condition of adult males and females across each season, changes in the temporal availability of better conditioned mates does not account for the assortative mating were found. Males found in amplexus were also generally of poorer condition, which may occur as individuals investing more heavily into higher-signalling effort are more successful in finding a mate but at the expense of maintaining current condition. We propose that both findings could be evidence of active mate choice in an explosive breeding species. Our findings highlight the need to consider mate condition alongside size to detect the presence of assortative mating or non-random mating among explosive breeding amphibians.